Creating a robust multidisciplinary public health workforce — almost there?. (21st November 2022) - Sim, Fiona; Wright, Jenny; Ferguson, Katie
Abstract: From 1972 to 2001, membership of the Faculty of Public Health (FPH) was only open to medical practitioners with recognised specialist experience or training in public health. In 2001, the Faculty became multidisciplinary at the specialist level, a rare achievement in a medical specialty in the UK. 1 Specialists from backgrounds other than medicine were accepted as Members and Fellows of the Faculty provided they met the required standards. They were eligible for Consultant and Director of Public Health (DPH) posts, initially in England and Wales. A multidisciplinary higher specialist training scheme was established and, over time, rolled out systematically across the UK. These changes later led to limited developments for public health practitioners filling roles distinct from those in the specialist workforce. Reviewing this history reminds current and future generations of the struggles to reach the unique model we have today. The article teases out the key factors leading to the changes, summarises the somewhat bumpy journey over five decades and, in the shadow of the pandemic, reflects on the contemporary situation for the UK's public health workforce.